Effect of weft parameters on weaving performance and fabric properties - Haque, Md Mahbubul (Daffodil International University Journal of Science and Technology, 2010)
Threads per inch and yarn count are some of the most important parameters that affect both weaving performance and fabric property. Experimental studies were conducted by weaving fabrics with three different picks per inch (PPI) and weft counts. The study shows that weaving performance is affected by the too high cover factor. Cover factor was calculated by dividing the threads/inch by the square root of the English cotton count and end breakage was taken as an indication of weaving performance. It was observed that when the count as well as threads/inch of one series of yarn changes the crimp% i.e. the consumption of both series of yarns are affected. It was also observed that, as expected, when the threads/inch increases the fabric strength also increases but at higher threads/inch the gain in strength is relatively more. Keywords: Threads, cover factor, EPI, PPI, crimp, strength, weaving performance DOI: 10.3329/diujst.v4i2.4369 Daffodil International University Journal of Science and Technology Vol.4(2) 2009 pp.62-69